Enhancement of Supercritical Water Oxidation by Dihydric Alcohol - Al-Kaabi , Falah Kareem Hadi (Current Topics and Emerging Issues in Chemical Science Vol. 2, 2023)
Supercritical water oxidation (SCWO) serves as an advanced technique predominantly applied for the management of stable organic wastes. The investigation aimed to explore the application of two types of alcohols, namely propylene glycol (PG) and isopropyl alcohol (IPA), as co-fuels. The purpose was to assess their effectiveness in the destruction of 3-methylpyridine by utilizing hydrogen peroxide as the primary source of oxygen. The experiments were conducted in a plug flow reactor under a pressure of 25 MPa and at temperatures ranging from 425 to 525ºC, with residence times varying from 6 s to 14 s. The results were analyzed in terms of total organic carbon (TOC) removal as a function of time and various process parameters. The results showed that propylene glycol had a positive effect on the destruction of 3-methylpyridine, with TOC removal reaching \(\ge\) 97.5% at 525ºC and 14 s. The highest TOC removal efficiency of 93% was achieved at 425ºC, 14 s, and a [propylene glycol]/[3-methylpyridine]o ratio of 3. Furthermore, the presence of propylene glycol improved the removal efficiency of nitrogen, which reached 89% at 525ºC and 10 s. The oxidant ratio was also found to have a positive effect on the removal of TOC in all three systems. Propylene glycol showed a greater impact on the ratio at 425ºC than isopropyl alcohol, owing to the two hydroxyl groups in propylene glycol's oxidation, which generate various free radicals and enhance the reaction.